Reproductive Traits and the Physiological Background of the Seasonal Variations in Egyptian Suffolk Ewes under the Conditions of Egypt - Marai, I F M; El-darawany, A A; Abou-Fandoud, E I; Abdel-Hafez, M A M (Annals of Arid Zone, 2016)
The calculated temperature-humidity index indicated absence of heat stressduring winter and exposure to very severe heat stress during summer and to severeheat stress during autumn, under the sub-tropical conditions of Egypt. Cervical mucuspH was lower significantly (P